SQ3R Method for Teaching Reading Narrative Text of the Tenth Grades at MA IslamiyahTanggulangin - Ainun Mujidah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine the effect of learning to read students using SQ3R method with student who don’t use the SQ3R method. The problem in this research is the difficulty of students in identifying a problem in a narrative reading text to determine the character, character, and setting in a story. In this study using a true experimental design research design with two classes in the control class and experimental class and two different treartment namely using treatment and not using treatment. In the control class in order to determine the effect on the two classes of researcher. On the result of the calculation of the classes in the control and experimental class there is a significant effect of students reading learning after being taught using the SQ3R method. Thus Ha: there is no significant effect of students reading learning after being taught using the SQ3R method. Ho: there is a significant effect of students reading learning after being taught using SQ3R method. In this explanation, it is evident that there is an influence of learning to read using the SQ3R method.